Determinants of digital health literacy among older adult patients with chronic diseases: a qualitative study - Shao, Yujiao; Yang, Xiumu; Chen, Qin; Guo, Hongyan; Duan, Xiaocui; Xu, Xuejun; Yue, Jianxing; Zhang, Zeyu; Zhao, Shuang; Zhang, Shiqing (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to identify the factors influencing digital health literacy in older adult patients with chronic diseases.MethodsA descriptive qualitative approach incorporated purposive and snowball sampling methods. Semi-structured interviews were conducted with 32 older adult patients with chronic diseases from three hospitals in Anhui Province between October 2023 and May 2024. Data were coded and analyzed using Nvivo 12.0 software and content analysis.ResultsTwo main themes and nine subthemes emerged: driving factors: these include the accessibility of digital health resources, perceived value and management needs, family economic and social benefits, and social network support systems. Restricting factors: These include cognitive blind spots and understanding biases, basic skills and challenges in digital adaptation, psychosocial limitations, issues with health information quality, and concerns about digital security risks.ConclusionThe digital health literacy of older adult patients with chronic diseases is generally low, characterized by cognitive blind spots, and influenced by various personal and social factors. It is recommended to engage social forces, optimize the accessibility and applicability of digital health resources, create a supportive digital health environment, and help older adult patients improve their digital health literacy to enhance chronic disease self-management through digital health technology.